A comparative analysis on conceptual design model of assistive courseware (AC) for visually-impaired learners (AC4VI) - Aziz, Nurulnadwan (INSInet Publications, 2014)
This paper reports on an ongoing study which intends to propose a conceptual design model of Assistive Courseware (AC) that is specifically designed for Visually-impaired (VI) learners.Through a systematic review and preliminary investigation, this study finds that numerous studies have been carried out related to courseware development either for normal learners or disabled learners.However, the studies interrelated with the development of conceptual design model of AC that is specifically designed for VI learners are highly scares. This is proven through analyzing ten existing models of AC.This paper aims at (i) analyzing the existing conceptual design models of AC and (ii) identifying the common components of conceptual design model of AC for VI learners.Briefly, findings of this study reveal that the conceptual design model of AC for VI learners is highly lacking. In addition, ID model, learning theories, and learning approach act as the basic components in designing a conceptual design model of AC for VI learners